Helminth infections among long-term-residents and settled immigrants in Qatar in the decade from 2005 to 2014: temporal trends and varying prevalence among subjects from different regional origins. Issue 1 (December 2016) - Abu-Madi, Marawan; Behnke, Jerzy; Boughattas, Sonia; Al-Thani, Asma; Doiphode, Sanjay; Deshmukh, Anand
Abstract Background Travel and migration from developing regions, where tropical diseases are common, to more developed industrialised nations can contribute to the introduction and subsequent spread of infections. With its rapidly expanding economy, Qatar has attracted vast numbers of immigrant workers in the last two decades, often from countries with poor socio-economic levels. Many used to arrive with patent intestinal parasitic infections. Methods We analysed the prevalence of helminth infections in a dataset of 29, 286 records of subjects referred for stool examination at the Hamad Medical Corporation over the course of a decade (2005 to 2014, inclusive). Results Overall prevalence of combined helminth infections was low (1.86 %) but there were significant temporal trends, age and sex effects and those arising from the region of origin of the subjects. The most common helminths were hookworms (overall prevalence 1.22 %), which accounted for 70.1 % of cases, and therefore patterns for combined helminth infections were largely driven by hookworms. In both cases, and also inTrichuris trichiura andAscaris lumbricoides, prevalence peaked in 2008, since when prevalence has been steadily falling. Helminth infections were largely concentrated among subjects from five Asian countries (Nepal, Bangladesh, Sri Lanka, India and Pakistan), and there was a highly biased prevalence in favour of male subjects in all cases. Prevalence of all three nematodes peaked in age class 7 (mean age 25.5 years, range = 20–29) and there were significant interactions between region of origin, sex of subjects and prevalence of hookworms. Conclusion These results offer optimism that prevalence will continue to decline in the years ahead, especially if control is targeted at those most at risk of carrying infections.